(untitled) (The Batuk, 2023)
The study aims to investigate the factors affecting entrepreneurial intentions of master level business students in addition to the moderating effect of selected demographic factors. Consolidation of theory of planned behavior and self-efficacy, the study used analytical research design to investigate and analyze the predictors of entrepreneurial intentions among the Master’s Degree Business Management students. Validated questionnaire was used for the survey from the 248 students. Descriptive and inferential statistics were used to test sample adequacy and testing hypotheses. The study concluded with significant positive impact of educational support, subjective norms, need for achievement and risk-tolerance on entrepreneurial intentions of students with some selected moderating influences of gender, family background and family and friends support. The study refuted the gender influence in entrepreneurial intentions of management students while significant positive influence of business family background, and family and friend support. The findings of the study are applicable for universities and policy makers for the implementing entrepreneur-oriented course, assignments and evaluation models to create entrepreneurial intentions among the future business owners, managers and business developers. This study has covered the total population of a particular course offered by a university which provided evidence for the originality of the study.